KONSELING KELOMPOK EMOTIONAL INTELLEGENCE PADA TIPE KEPRIBADIAN INTROVERT - Ainun Sakinah (Universitas Islam Negeri Mataram, 2018)
Counselling groups in practice put more emphasis on the attitude of openness and trust and the attitude of maintaining secrecy than individual counselling, so group counselling was able to facilitate individuals to develop an attitude of openness. Different personality types are different in managing their emotions. Likewise, the type of introvert and extrovert personality, if extroverts tend to be ?exible and easy to socialize, introverts are not. Personal introverts that are identical with closed attitudes and lack of socialization. But some introverts develop emotions so they are able to adapt to the new environment, even though for that they need more time to reach that stage. This research is a type of library research or library research, using a reference analysis approach. Based on this research, introverted emotional intelligence is understanding the environment, planning approaches, doing what has been planned well, then evaluating the steps that have been taken. So that introverts have good emotional intelligence with a detailed process called relational understanding.